Austria : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper presents details of Austria's 2013 Article IV Consultation. Austria has been growing economically but is facing challenges in the financial sector. Full implementation of medium-term fiscal adjustment plans require specifying several measures and plans that need gradual strengthening to take expected further bank restructuring cost into account. It suggests that strong early bank intervention and resolution tools, a better designed deposit insurance system, and a bank-financed resolution fund would help reduce the need for budgetary support to any troubled banks in the future.